Kepemimpinan Transformasional dan Budaya Organisasi: Dampaknya terhadap Motivasi, Kepuasan, dan Kinerja Karyawan BUMDES - Maulinda Hasanah; Samsuki (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
BUMDes, as drivers of the village economy, play a strategic role in improving community welfare, including in Pamekasan Regency, which is rich in local potential. However, many BUMDes still face institutional challenges, low work motivation, and suboptimal employee performance. Internal factors such as transformational leadership style and organizational culture are thought to play an important role in shaping employee motivation, satisfaction, and performance. This study aims to analyze the influence of transformational leadership style and organizational culture on work motivation and its impact on job satisfaction and employee performance in BUMDes in Pamekasan Regency. The study uses a quantitative method with an explanatory research approach. The population includes 23 BUMDes, with 108 respondents determined using the Lemeshow formula. Data were collected through questionnaires and interviews, then analyzed using Smart-PLS. The results showed that transformational leadership style and organizational culture had a positive and significant effect on work motivation. Work motivation has a significant effect on job satisfaction and acts as a mediator in improving employee performance. Transformational leadership and job satisfaction also have a direct effect on employee performance, while organizational culture has an indirect effect through motivation and job satisfaction. These findings emphasize the importance of strengthening leadership and organizational culture to improve the quality of human resources and the sustainability of BUMDes.